Buku Ilustrasi Digital sebagai Media untuk Meningkatkan Kemampuan Numerasi Siswa dalam Bahasa Inggris - Rahma Nasir; Siti Nurjannah; Nadila Frensiska Amanda; Adria; Nofianti (Pendidikan Matematika FKIP Universitas Mataram, 2023)
This article examined the English numeration conditions in the elementary school in Duyu, Palu, Central Sulawesi where the lack of learning media for numerical development. This highlights the need to combine visual learning approaches, such as the use of pictures related to numbers, to facilitate numerical mastery. While numeration is vital to life, many students still face the challenge of learning numeration and especially in English. The study involves qualitative descriptive methods. The purpose of this study is to find out the role of digital books and the impact they have on numerical cultures in today's era. The study suggests that the use of illustrated digital books has a positive effect on the ability to understand arithmetic. Students involved in illustrated digital books show an increased understanding of numbers, as interactive features and multimedia elements provide context, support, and involvement during the learning process. The integration of digital books means to improve student literacy not only enhances reading comprehension and language development but also tackles urgent problem of alignment and access to education.